Bay-Region-Selective Annulative π-Extension (APEX) of Perylene Diimides with Arynes - Nakamuro, Takayuki; Kumazawa, Kazushi; Ito, Hideto; Itami, Kenichiro (Synlett, 2019)
A bay-region-selective annulative π-extension (APEX) reaction of perylene diimides (PDIs) has been achieved by means of in-situ generated reactive aryne intermediates. This method provides an efficient one-pot π-extension at the short axis of PDIs in a sequential manner. Mechanistically, an inverse-electron-demand Diels–Alder reaction might be operative for the transformation.
Keywords: annulative π-extension; perylene diimides; arynes; Diels–Alder reaction; coronene diimides; polycyclic aromatic hydrocarbons